(Imagining) Science for Troubled Times: A Mouse, a Bird, and a Threshold for Collaboration - Carlson, Rebecca (Imaginations, 2021)
Although biological life and human social complexity are fundamentally interdependent, biological and social researchers continue to perceive each other from across divides of theoretical, methodological, and institutional skepticism. This paper considers conversational boundary work between qualitative and quantitative scientists as an institutionalized rhetorical performance which throttles their cooperation, even in the face of the COVID-19 pandemic when it is most urgently needed. As an example, I look at the way familiar epistemological conflicts emerged out of collaboration between myself and a bioscientist during the spring of 2020, when co-participating in the Massive Microscopic Sensemaking Project, a 21-day international auto-ethnographic writing experiment.